Asbestos‐related lung cancer: Clinical characteristics and survival outcomes in an Australian cohort seeking workers compensation. Issue 5 (31st January 2022) - Hyland, Rebecca A; Chrzanowska, Agata; Hannaford‐Turner, Kirsty; Davis, Alexander; Ke, Helen; Bradbury, Lauren; Nagrial, Adnan; McCaughan, Brian; Hui, Rina; van Zandwijk, Nico; Takahashi, Ken; Kao, Steven C
Abstract: Background and objectives: Due to difficulties in identifying sufficient‐sized cohorts there remains uncertainty about prognostic and clinical differences that may be unique to asbestos‐related lung cancer (ARLC). In this study, we use the Helsinki Criteria to define a group of ex‐workers with lung cancer attributable to asbestos exposure and investigate differences that may exist. Methods: A total of 529 patients seeking workers' compensation for their lung cancer were assigned to either ARLC or the non‐ARLC based on parameters defined in the Helsinki Criteria. Clinical and survival details were collected and analyzed. Results: In our study population, ARLC patients were on average older (72.1 ± 7.8) than non‐ARLC patients (66.5 ± 10.2, P < 0.001) and were more likely to be diagnosed as a result of incidental findings or screening program ( P < 0.001). The groups were similar in terms of clinical characteristics with the only difference being that plaques were more prevalent among ARLC patients ( P < 0.001). Differences were observed for median overall survival (OS), ARLC (9 months) and non‐ARLC (13 months, P = 0.005), as well for treatment ( P = 0.01). After adjusting for age, however, these differences disappeared. Conclusions: Age at diagnosis, pleural plaques, and asymptomatic presentation were the attributes that we identified as significantly different between asbestos‐related cancer and other lung cancers. In this cohort, ARLC patients were older diagnosis and with worse overall survival. Abstract : Asbestos related lung cancer (ARLC) more commonly associated with older age, incidental diagnosis and presence of pleural plaques. ARLC less likely to have treatment and associated with shorter overall survival. This difference is not significant when adjusted for age.